Development of Systematic Parameter Optimization for Cryopreservation Protocols for Cellular Suspensions - Hofmann, N.; Bernemann, I.; Pogozhykh, D.; Glasmacher, B. (Problems of Cryobiology and Cryomedicine, 2011)
Effective cryopreservation of cellular suspensions is an important task of cryobiology. A systematic parameter optimization setup for cryopreservation of cellular suspensions was established on the basis of our previous studies. Keratinocytes were used as a cellular model. The investigation included 48 protocols with different cooling rates (B) in a two-step freezing protocols (B1 in the range of 4°C to –30°C and B2 from –30°C to –80°C). All protocols have been studied with four different concentrations of the most frequently applied cryoprotective agent dimethyl sulfoxide (DMSO). Raster analysis of approximately 600 samples allowed the detection of the most comprehensive array of possible variables. In further investigations this setup was used to improve the cryopreservation protocols for HPMEC-ST1.6R (human pulmonary microvascular endothelial cells). Results revealed that only an optimal combination of cooling rates ensured the highest survival rates of cells after thawing. In case of keratinocytes, the optimal freezing protocol was composed of the cooling rates of 5 K/min for B1 and 7.5 K/min for B2, or 5 K/min for B1 and 10 K/min for B2 (2.5% DMSO concentration). The highest survival rates of HPMEC-ST1.6R cell culture were achieved with application of the following protocols: 5 K/min (B1) combined with 5 K/min (B2) (7.5% DMSO); 3 K/min, combined with 3 K/min (5% or 7.5% DMSO); and 10 K/min combined with 3 K/min (10% DMSO).